Mathematics preservice teachers’ argumentation (2017)
ABSTARCT: This research deals with the preservice teachers’ dialogic argumentationswhen presenting geometry tasks to their colleagues, during discussion sessions previous to teaching to children. An argumentation analysis tool is used that complement Toulmin’s analysis proposal and that includes features related to mathematicallogic, rhetoric and dialectic features.We propose both a representation for the dialogic argumentation and a way to identify its structural qualities